Epigenetic Alterations and an Increased Frequency of Micronuclei in Women with Fibromyalgia. (22nd August 2013) - Menzies, Victoria; Lyon, Debra E.; Archer, Kellie J.; Zhou, Qing; Brumelle, Jenni; Jones, Kimberly H.; Gao, G.; York, Timothy P.; Jackson-Cook, Colleen
Abstract : Fibromyalgia (FM), characterized by chronic widespread pain, fatigue, and cognitive/mood disturbances, leads to reduced workplace productivity and increased healthcare expenses. To determine if acquired epigenetic/genetic changes are associated with FM, we compared the frequency of spontaneously occurring micronuclei (MN) and genome-wide methylation patterns in women with FM (n = 10 ) to those seen in comparably aged healthy controls (n = 42 (MN); n = 8 (methylation)). The mean (sd) MN frequency of women with FM (51.4 (21.9)) was significantly higher than that of controls (15.8 (8.5)) (χ 2 = 45.552 ; df = 1; P = 1.49 × 10 - 11 ). Significant differences (n = 69 sites) in methylation patterns were observed between cases and controls considering a 5% false discovery rate. The majority of differentially methylated (DM) sites (91%) were attributable to increased values in the women with FM. The DM sites included significant biological clusters involved in neuron differentiation/nervous system development, skeletal/organ system development, and chromatin compaction. Genes associated with DM sites whose function has particular relevance to FM included BDNF, NAT15, HDAC4, PRKCA, RTN1, and PRKG1. Results support the need for future research to further examine the potential role of epigenetic and acquired chromosomal alterations as a possible biological mechanism underlying FM.